Federal Educational Assistance Programs Available to Service Members Program Features and Recommendations for Improved Delivery - Buryk, Peter (RAND Corporation, 2015)
A variety of programs provide educational assistance to military service members, ranging from examinations that provide college credit for knowledge and experience gained in the military to various kinds of tuition assistance and student aid. RAND reviewed major federal-level educational assistance programs to provide an overall view of the system and suggest ways to assess it and help manage individuals' use of the programs.